Tribute to John B. Goodenough: From Magnetism to Rechargeable Batteries. Issue 2 (3rd June 2020) - Mauger, Alain; Julien, Christian M.; Armand, Michel; Zaghib, Karim
Abstract: In macroeconomics, the rate of economic growth in the world is a historical phenomenon, which will mark the 20th century. It was made possible by an increasing consumption of fossil fuel. However, not only are these resources limited and unrenewable, but combustion has dramatic side effects such as emission of greenhouse gases responsible for global warming and change of climate. As a consequence, major efforts have been taken to move away from fossil fuels and switch to renewable energy including solar and wind energy. These energy sources, however, are intermittent and can be integrated into the electrical network only after regulation. Electrochemical storage is a key solution to regulate these intermittent sources of energy into smart grids. Although governments have only recently become aware of this problem, some scientists have been focusing their attention on rechargeable batteries since the 1970s, and it took until 2019 for the Nobel committee to award the Nobel prize to those who paved the path to their development. John B. Goodenough is one of the three winners of this Nobel prize, for his pioneering research on lithium‐ion batteries (LIBs). The impact of LIBs includes the development of rechargeable hybrid and electric vehicles at the expense of gasoline cars. Before the 1970s, however, John B. Goodenough had already made major contributions to materials science as a solid state physicist, including the investigation of the interplay between the magnetic and transport properties of perovskites. It is the purpose of the present work to report a brief review of the scientific works of John B. Goodenough, through selected works that demonstrate his mastery of chemistry and physics. Abstract : Prof. John B. Goodenough's life achievements: from magnetism to rechargeable lithium batteries.